The Teacher as Leader: Effect of Teaching Behaviors on Class Community and Agreement - Rubin, Beth; Fernandes, Ronald (International Review of Research in Open and Distributed Learning, 2013)
This article examines the effects of teaching behaviors in online university classes, focusing on the agreement among class members. Literature on group leaders’ effects on group agreement about workplace climate is reviewed. Hypotheses are generated about the effects that teachers of online courses, as class leaders, have on both the level and agreement about the community of inquiry. They are tested with a sample of 874 students in 126 online courses. The aggregate class level and strength of agreement about the teaching presence have significant effects on the level and agreement about cognitive presence and social presence. Although the aggregate levels and agreement about community of inquiry are related, different patterns emerge. The paper explores the interaction effects of level and agreement, finding that in classes with high levels of teaching presence, the higher the agreement about teaching presence, the higher the agreement about cognitive and social presence especially for classes reporting stronger levels of cognitive and social presence. In classes with lower levels of teaching presence, agreement has a different effect.